SWOT Analysis: How Compact Curricular Agenda affects English Teaching and Learning Process - Nyak Mutia Ismail; Juliana Juliana; Rusma Setiyana; Hayatul Muna (Proceedings of AICS - Social Sciences, 2016)
A successful process of English teaching and learning has been considered as an ultimately major goal in Indonesian high-schools, including in integrated Islamic high-schools known with doubled-curriculum schools. To mention further, this agenda tightens students’ academic activities as other subjects also bring about numerous high standard motives and goals. This study was conducted to analyze the effect of this compact curricular agenda towards the process of English Teaching and learning from the teacher’s perspectives. The curricular agenda at SMP IT Az-Zahra Takengon was SWOT-analyzed regarding its effect to the process of English teaching and learning at the school. In significance, this study is expected to broaden the knowledge of stakeholders of high-school curriculum management in developing the curricular academic activities in more deliberately careful ways in the purpose of reaching the goal protocols. The method used in this study was mainly qualitative approach through interviews which solely sheds light on the description of the academic agenda in the congruence of English teaching and learning process through interviews with the English teacher at the school. The result showed that the strength is that it has risen the students’ motivation whether in learning English or other subjects since the school provides various curricular activities, instead of monotonous ones, that loosen the students’ boredom and tension. The weakness is that full academic agenda leads to the condition where lots of English lessons are left untaught from which we eventually see that it are a management failure. The opportunity from the agenda is that the students are exposed to multi-disciplinary material abundance. Finally, the thread is that realizing the students with low motivation in English would seemingly remove English into their blacklists as a result of exhaustion.